2022
DOI: 10.1002/smtd.202200853
|View full text |Cite
|
Sign up to set email alerts
|

Design Strategies of Tumor‐Targeted Delivery Systems Based on 2D Nanomaterials

Abstract: Conventional chemotherapy and radiotherapy are nonselective and nonspecific for cell killing, causing serious side effects and threatening the lives of patients. It is of great significance to develop more accurate tumor‐targeting therapeutic strategies. Nanotechnology is in a leading position to provide new treatment options for cancer, and it has great potential for selective targeted therapy and controlled drug release. 2D nanomaterials (2D NMs) have broad application prospects in the field of tumor‐targete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 184 publications
0
10
0
Order By: Relevance
“…Therefore, it is the key to effectively preventing the unwanted leakage of anticancer agents and improving the targeted delivery. [ 22 ]…”
Section: Targeted Nanomaterials Without a Stimulus‐response For Cance...mentioning
confidence: 99%
“…Therefore, it is the key to effectively preventing the unwanted leakage of anticancer agents and improving the targeted delivery. [ 22 ]…”
Section: Targeted Nanomaterials Without a Stimulus‐response For Cance...mentioning
confidence: 99%
“…Rare examples were reported to develop effective strategies for controlling the stacking patterns of fluorophores facilitating [2+2] photocycloaddition reaction, but it was demonstrated that this intermolecular photoreaction can efficiently take place when the stacking patterns of the fluorophores were arranged in a right way using DNA or MOFcontrolled assembly (Fig. 22), 115,116 and thus more efforts should be devoted to regulating molecular packing of fluorophores in a controllable manner.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Extensive efforts have been devoted to enhancing the antitumor efficacy of nanocarriers to deliver an effective drug therapy strategy, such as the active targeting strategy and stimuli-responsive nanosystem . Recently, a cell membrane (cM)-coating bionic strategy has emerged that endows nanocarriers with homologous cell biological functions .…”
Section: Introductionmentioning
confidence: 99%